2019
DOI: 10.1021/acs.jpcc.9b08903
|View full text |Cite
|
Sign up to set email alerts
|

High-Energy Optical Transitions and Optical Constants of CH3NH3PbI3 Measured by Spectroscopic Ellipsometry and Spectrophotometry

Abstract: Optoelectronics based on metal halide perovskites (MHPs) have shown substantial promise, following more than a decade of research. For prime routes of commercialization such as tandem solar cells, optical modeling is essential for engineering device architectures, which requires accurate optical data for the materials utilized. Additionally, a comprehensive understanding of the fundamental material properties is vital for simulating the operation of devices for design purposes. In this article, we use variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 64 publications
(142 reference statements)
0
4
0
Order By: Relevance
“…Excellent agreement between theory and experiment is obtained for both the shape and the width of the curve. The possible transitions were extracted from the second-derivative spectra of ε 2 using the method of critical point (CP) analysis. , The origin of the transitions was determined from the band structure of CsPbBr 3 (Figure c and Table ). E a in both cases corresponds to the excitonic band-edge transitions ( R → R ); the rest originates from the transitions to the conduction band from different states in the valence band.…”
Section: Resultsmentioning
confidence: 99%
“…Excellent agreement between theory and experiment is obtained for both the shape and the width of the curve. The possible transitions were extracted from the second-derivative spectra of ε 2 using the method of critical point (CP) analysis. , The origin of the transitions was determined from the band structure of CsPbBr 3 (Figure c and Table ). E a in both cases corresponds to the excitonic band-edge transitions ( R → R ); the rest originates from the transitions to the conduction band from different states in the valence band.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental analyses have also been reported by means of ultraviolet-visible optical absorption and transmittance spectroscopies, 59,60 spectroscopic ellipsometry, and spectrophotometry. [60][61][62] In the tetragonal phase (∼160-330 K), Onoda-Yamamuro et al 63 and Mohanty et al 64 measured the static dielectric constant at 1 MHz by IS vs temperature with ε 60 À 120 and thermal gradients @ε/@T À0:3 K À1 . At room temperature, Ding et al 30 showed ε spectrum above 50 too.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
“…The main method for determining the optical constants of halide perovskites is ellipsometry of thin polycrystalline films. Although this method provides both the imaginary and the real part of the dielectric constant of the material, it is extremely sensitive to the state of the sample surface: its roughness, the presence of contamination, or an oxide layer. Thin perovskite films may have a surface of fairly high optical quality, but results of optical measurements will greatly depend on the film manufacturing method, the size, and orientation of its constituent grains.…”
Section: Introductionmentioning
confidence: 99%
“…In a number of works, ellipsometry has been applied to perovskite single crystals. Alternative methods for determining the optical constants of perovskites are simultaneous reflection and transmission measurements , and Brewster angle measurements from polished or natural facets of single crystals . The listed approaches were used to determine the optical constants of the most studied iodide perovskite MAPbI 3 ,,,,, and mixed-cation (MA,FA)­PbI 3 , bromide perovskites CsPbBr 3 , ,, MAPbBr 3 and FAPbBr 3 , , and chloride perovskite MAPbCl 3 . Most of the above-mentioned studies were performed at room temperature or in its close vicinity, with the exception of cryogenic studies from 4 K for MAPbBr 3 and (MA,FA)­PbI 3 and from 77 K for MAPbI 3 …”
Section: Introductionmentioning
confidence: 99%